University students’ awareness of the effects of the phenomenon of endogamy in Omani society - Al-Dari’i, Mohammed; Saleh, Emad Farouk; Mostafa, Magdy Mohamed (Al-Adab Journal, 2022)
The present study deals with the problem of endogamy in Omani society; thus, the study aimed to determine the level of university students’ awareness concerning the implications of the phenomenon of endogamy (knowledge – attitudes – practices), It adopted a methodology strategy that relied on the use of the descriptive and analytical approach that was applied using the comprehensive social survey method on students of Sultan Qaboos University in all academic years in all practical and humanitarian specializations, whose number reached (15727) students, and the data was collected by relying on the main tool of the study (electronic scale). The study found a set of results, the most important of which are: A strong level of knowledge among university students about the effects of endogamy. The results also showed a strong level of university students’ attitudes towards the impact of consanguineous marriage. At the same time, the results indicated that university students’ level of actual practice in dealing with the effects of endogamy was medium. Hence, the overall outcome of awareness of the impact of endogamy indicates that it is a substantial level. Finally, the study presented a set of proposals, the most important of which is the need for the social work profession to focus on studying the phenomenon of endogamy and its implications. Moreover, there is a need for the social work profession to give more attention through research interests and research projects to the phenomenon of endogamy. The study also draws attention to the importance of focusing on marriage in general and endogamy in particular through non-classroom activities and the activities of student groups at the university. A set of practical mechanisms has been attached to each study proposal. It can be used to raise the level of university students’ awareness in particular and community awareness about the harmful effects of the phenomenon of endogamy and how to reduce its impact.